Murder of an open book : a Scumble River mystery - Swanson, Denise (Swanson, Denise. Scumble River mysteries., 2015)
"A nasty faculty feud leaves one Scumble River teacher belly-up. . . . Her honeymoon may have been less than relaxing, but Skye Boyd née Denison is still high on marital bliss with her new husband, Wally. The fact that their family is about to get bigger is even more exciting, even if Skye is dealing with morning sickness--and trying to hide the news from her ever-meddling mother, May. But Skye quickly comes crashing down from cloud nine when the body of one of her coworkers, science teacher and volleyball coach Blair Hucksford, is found in the school swimming pool. The troublesome trainer was on the bad side of almost everyone on staff and many of the girls on her team, leaving Skye to sort through a huge roster of suspects. Now she must figure out which wronged party was mad enough to kill, and quickly--before someone else in town gets bumped off" --